KAJIAN KESULITAN BELAJAR MAHASISWA DALAM KEMAMPUAN PEMBUKTIAN MATEMATIS DITINJAU DARI ASPEK EPISTEMOLOGI PADA MATA KULIAH GEOMETRI TRANSFORMASI - Mohammad Dadan Sundawan (Program Studi Pendidikan Matematika FKIP Universitas Islam Darul Ulum, 2018)
This research specifically aims to analyze the ability of mathematical proof, to analyze learning difficulties in terms of student epistemology on the material of transformation geometry. The long-term benefit of this study is the study of learning difficulties in terms of student epistemology related to mathematical proofing in the course of transformation geometry, is expected to provide encouragement to other lecturers to further develop the learning process or teaching materials in an effort to develop mathematical proof of mathematics students. This research uses descriptive method, while the subject of research is 9 students of Unswagati mathematics teacher candidate who contracted the course of transformation geometry. Methods of data collection used include: (1) test of mathematical proof capability; (2) observation; (3) interviews; and (4) documentation. The research results obtained there are 5 kinds of student difficulties viewed from epistemology related to the geology of transformation geometry, namely a) difficulty learning related difficulties in applying the concept; b) learning difficulties related to visualizing geometric objects; c) learning difficulties with difficulty in determining principles; d) learning difficulties related to understanding problems and e) related difficulties in mathematical proofing. Especially in mathematical proofing, students have difficulties such as: not knowing how to start construction of evidence, unable to use known concepts and principles, and tend to start construction of evidence with what must be proven.